A comprehensive review and update on human fertility cryopreservation methods and tools - Antonouli, Sevastiani; Di Nisio, Valentina; Messini, Christina; Daponte, Alexandros; Rajender, Singh; Anifandis, George (Frontiers in Veterinary Science, 2023)
The broad conceptualization of fertility preservation and restoration has become already a major concern in the modern western world since a large number of individuals often face it in the everyday life. Driven by different health conditions and/or social reasons, a variety of patients currently rely on routinely and non-routinely applied assisted reproductive technologies, and mostly on the possibility to cryopreserve gametes and/or gonadal tissues for expanding their reproductive lifespan. This review embraces the data present in human-focused literature regarding the up-to-date methodologies and tools contemporarily applied in IVF laboratories' clinical setting of the oocyte, sperm, and embryo cryopreservation and explores the latest news and issues related to the optimization of methods used in ovarian and testicular tissue cryopreservation.